Regulations and Applications of Ethics in Business Practice (Accounting, Finance, Sustainability, Governance & Fraud: Theory and Application,, 2018)
This book presents a variety of discussions from different countries about regulations and applications of ethics in business practice. It demonstrates how Ethics, both in the world of business and in academic life, is consistently a central and unavoidable issue that institutions must devise new regulations on a regular basis to address. Given that applying such regulations becomes complicated in a global business landscape and that International companies have lost large amounts of revenues due to fraudulent activities, the book provides insights for professionals in business world to teach, learn, apply, measure and report on companies' daily business. Business and Professional Ethics: Theories, Standards, and Analysis is essential reading for researchers and students in business schools around the world.